Investigating the Influence of Agency on Trust in a Collaborative Game-Based Scenario. (September 2017) - Proaps, Alexandra B.; Long, Shelby K.; Liechty, Molly; Bliss, James P.
This study is part of an ongoing investigation into the ways in which individual differences may interact with game characteristics to impact performance and subjective trust outcomes within virtual environments. In this study, researchers investigated the impact of team leader agency on trust and performance. Forty college students were told they were working alongside a computer-programmed team leader or a human team leader who provided instructions for twelve tasks in a first-person shooter game, Arma 3™. Results indicate that team leader agency may not impact subjective trust using this type of experimental manipulation, but that intrinsic motivation is related to trust outcomes. Results also indicate differences in the number of times participants reviewed the team leader's task instructions as a function of agency. Implications for future research include measuring trust behaviorally and investigating whether game-based intrinsic motivation may mediate the relation between trust and performance.